ANALYZING COGNITIVE LEVELS AND CONSTRUCTIVE ALIGNMENT IN A SEVENTH-GRADE ENGLISH TEACHING MODULE - Amalia Zulfan Hadi; Tatu Siti Rohbiah; Eulis Rahmawati (INJOSEDU: International Journal of Social and Education, 2026)
This study investigated the cognitive levels and constructive alignment reflected in a seventh-grade English teaching module at SMPN 24 Tangerang. The study aimed to classify the cognitive levels of learning objectives, learning activities, and assessment tasks based on Bloom's Revised Taxonomy and to examine the alignment among these instructional components using Biggs and Tang's Constructive Alignment Theory. A qualitative document analysis was employed, supported by classroom observations and teacher interviews to triangulate data. The data were obtained from Chapter 5 (Units 1–3) of the English teaching module adapted from English for Nusantara. The findings revealed that most instructional components were categorized at the understanding (C2) and applying (C3) levels, indicating the predominance of Lower Order Thinking Skills (LOTS). Nevertheless, one assessment task reached the evaluating level (C5) and two tasks reached the creating level (C6), showing limited integration of Higher Order Thinking Skills (HOTS). The study also found that the instructional components were generally aligned, although several assessment tasks required higher-order cognitive processes than those specified in the learning objectives.